TEOA Inhibits Proliferation and Induces DNA Damage of Diffuse Large B-Cell Lymphoma Cells Through Activation of the ROS-Dependent p38 MAPK Signaling Pathway - Yu, Xingxing; Wang, Xin; Wang, Xu; Zhou, Yi; Li, Yanchun; Wang, Aiwei; Wang, Tongtong; An, Yihan; Sun, Weidong; Du, Jing; Tong, Xiangmin; Wang, Ying (Frontiers in Pharmacology, 2020)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of lymphoma, accounting for approximately 30% to 40% of non-Hodgkin’s lymphomas (NHL). The administration of rituximab significantly improved the outcomes of DLBCL; however, the unavoidable development of resistance limits the long-term efficacy. Therefore, a new generation of less toxic drugs with higher chemotherapy response is required to prevent or reverse chemoresistance. TEOA is a pentacyclic triterpenoid compound isolated from the roots of Actinidia eriantha. Studies have confirmed that TEOA has significant cytotoxicity on gastrointestinal cancer cells. However, there are no relevant reports on DLBCL cells. In this study, we investigated the potential molecular mechanism of the anticancer activity of TEOA in DLBCL cells. The results demonstrated that TEOA inhibited proliferation and induced apoptosis in time-and dose-dependent manners. TEOA induced reactive oxygen species (ROS) generation, which was reversed by N-acetyl cysteine (NAC). TEOA induced DNA damage, increased the level of γ-H2AX, and the phosphorylation of Chk1 and Chk2. In addition, TEOA induced the activation of the p38 MAPK pathway and pretreated with p38 inhibitor SB20358 or ROS scavenger could block TEOA-induced DNA damage. Taken together, these results suggest that ROS mediated activation of the p38 MAPK signal pathway plays an important role in initiating TEOA-induced DNA damage.